An Overview on Development, Approval and Post Registration Activities for Pharmaceuticals in European Union - Thanush, D; V, Balamuralidhara; V, Thoyajaksha; S, Deeksha K; R, Gowthami K (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Bringing a new medicine from concept to market is costly and complex. Years of study and development go into it. Product development operations should be carried out in line with applicable regulatory standards to save time and money when bringing innovations to the marketplace. While the information on regulatory requirements is readily accessible, navigating the regulatory system is complex and becomes considerably more difficult when working with many countries. The primary goal is to improve regulatory awareness and achieve regulatory compliance in product development. An excellent place to start is with one of these ideas. The guide is not a list of laws but a discussion of the foundational ideas and principles governing regulatory policymaking and enforcement in the European Union. Throughout the drug's lifespan, these rules are consistent. Companies may standardise their processes and keep track of every action at every step of the lifecycle by developing a workflow and adhering to its stages of lifecycle compliance for each set of guidelines. Because of the current pharmaceutical market's complexity, more efficient drug research and manufacturing are required. This review article is based on the information collected from various sources from EMA and ICH websites and the articles mentioned. Despite the extreme complexity, Product Lifecycle Management has the potential to make pharmaceutical manufacturing more efficient and less risky. Pharmaceutical product lifecycle management during various phases such as research and development, regulatory submission and approval, commercialisation and marketing plays a significant role.
Keywords: Product Lifecycle Management; Navigation Pathway; New Product Development; Post Approval Changes; Regulatory Review; European Union